Associations among psychosis, mood, anxiety, and posttraumatic stress symptoms: A network analysis. Issue 2 (2nd March 2023) - Astill Wright, Laurence; McElroy, Eoin; Barawi, Kali; Roberts, Neil P; Simon, Natalie; Zammit, Stanley; Bisson, Jonathan I
Abstract: The associations among psychotic experiences (i.e., hallucinations and delusions), trauma exposure, and posttraumatic stress symptoms are complex and multidirectional. Using network analysis to understand how psychotic experiences and symptoms of posttraumatic stress disorder (PTSD) relate to one another may identify new interventional targets to treat comorbidity and its underlying pathological processes. This study aimed to use network analysis to examine the associations among psychotic experiences; negative symptoms of psychosis; and symptoms of PTSD, anxiety, and depression. In this population‐based cohort study, 4, 472 participants (36.7% male) were assessed for psychotic experiences, negative symptoms of psychosis, PTSD, anxiety, and depression at age 23 ( M = 23.86 years, SD = 0.520) or 24 years ( M = 24.03, SD = 0.848). Associations among symptoms were assessed via network analysis. Exploratory graph analysis identified three clusters of densely connected symptoms within the overall network: psychotic experiences; PTSD symptoms; and depressive and anxiety symptoms and negative symptoms of psychosis. Psychotic experiences had the strongest associations with other symptoms in the network, and symptoms of anxiety played a key role in bridging psychotic experiences, symptoms of PTSD, and depressive symptoms. Consistent with the stress reactivity and affective models for psychotic experiences, the results suggest that symptoms of anxiety and emotional distress (e.g., hyperarousal, panic) may have a key role in the development and maintenance of psychotic experiences and symptoms of PTSD. Targeting these symptoms may ameliorate symptom burden transdiagnostically.